2003
DOI: 10.1136/pmj.79.931.297
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular fibrillation during electrical cardioversion of pre-excited atrial fibrillation

Abstract: The Wolff-Parkinson-White syndrome can rarely present with pre-excited atrial fibrillation. In this condition the short refractory period of the accessory pathway can lead to rapid atrioventricular conduction. There is then a danger that at high heart rates the irregular broad complex tachycardia that results can deteriorate into ventricular fibrillation. The initial management of patients presenting in pre-excited atrial fibrillation requires cardioversion to sinus rhythm. This can be performed by DC cardiove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…A recent study by Botkin et al found a complication rate of 2.6% 18 . Risks include stunning (which can occur after cardioversion by any method 19 ), failure to synchronize and thereby cause ventricular fibrillation, 20 aspiration pneumonia, pulmonary edema, and even fire (albeit during a defibrillation attempt) 21 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Botkin et al found a complication rate of 2.6% 18 . Risks include stunning (which can occur after cardioversion by any method 19 ), failure to synchronize and thereby cause ventricular fibrillation, 20 aspiration pneumonia, pulmonary edema, and even fire (albeit during a defibrillation attempt) 21 …”
Section: Discussionmentioning
confidence: 99%
“…Potential treatments include cardioversion and catheter ablation but both options have shortcomings. In addition to the fact that it provides only temporary relief from symptoms, external cardioversion is painful (Adlam & Azeem, ) and necessitates anaesthesia, which is expensive, time consuming, and can lead to complications (Boodhoo et al . ).…”
Section: Discussionmentioning
confidence: 99%
“… Separate input and output lines are required for the defibrillator to synchronise a shock. Pads and monitoring leads both need to be attached, and lead II should be selected as the input line. The ‘synch’ button should be pressed, and small symbols should designate each QRS complex on the defibrillation monitor. R on T phenomenon and ventricular fibrillation have been described as complications of synchronised shock In this event, administer a 200 J unsynchronised shock. …”
Section: Synchronisation Is An Essential Component Of the Process Andmentioning
confidence: 99%
“…lar fibrillation have been described as complications of synchronised shock. 25,26 • In this event, administer a 200 J unsynchronised shock.…”
Section: R On T Phenomenon and Ventricu-mentioning
confidence: 99%